Association of long COVID with housing insecurity in the United States, 2022-2023 - Samuel E. Packard; Ezra Susser (Elsevier, 2024)
Objectives: To assess the association of Long COVID with housing insecurity in the United States. Methods: To compare the prevalence of 3 binary indicators of housing insecurity between people with Long COVID (symptoms >3 months) and COVID-19 survivors who did not report long-term symptoms, we used survey-weighted regression models on 206,969 responses from the Household Pulse Survey, a representative cross-sectional survey of US households collected September 2022-April 2023. Among people with Long COVID, we additionally assessed whether functional impairment, current COVID-19 related symptoms, and symptom impact on day-to-day life were associated with a higher prevalence of housing insecurity. Results: During the study period, 56,353 respondents with prior COVID-19 experienced symptoms lasting 3 months or longer (27%), representing an estimated 28 million US adults. After adjusting for demographic factors, people with Long COVID were 1.5-2 times as likely to experience significant difficulty with household expenses (Prevalence ratio [PR] 1.48, 95% CI 1.42-1.55), be behind on housing payments (PR 1.48, 95% CI 1.36-1.60), and face likely eviction or foreclosure (PR 1.86, 95% CI 1.58-2.18). The risk of housing insecurity was highest among low-income adults with Long COVID. Among people with Long COVID, functional limitation and current symptoms which impact day-to-day life were associated with higher prevalence of housing insecurity. Conclusions: Compared with COVID-19 survivors who do not experience long-term symptoms, people with Long COVID are more likely to report indicators of housing insecurity, particularly those of lower socio-economic status, and those with functional limitations or long-term COVID-19 related symptoms impacting day-to-day life. Policies are needed to support people living with chronic illnesses following SARS-CoV-2 infection.